Adults with Chromosome 18 Abnormalities. Issue 4 (19th November 2014) - Soileau, Bridgette; Hasi, Minire; Sebold, Courtney; Hill, Annice; O'Donnell, Louise; Hale, Daniel E.; Cody, Jannine D.
Abstract: The identification of an underlying chromosome abnormality frequently marks the endpoint of a diagnostic odyssey. However, families are frequently left with more questions than answers as they consider their child's future. In the case of rare chromosome conditions, a lack of longitudinal data often makes it difficult to provide anticipatory guidance to these families. The objective of this study is to describe the lifespan, educational attainment, living situation, and behavioral phenotype of adults with chromosome 18 abnormalities. The Chromosome 18 Clinical Research Center has enrolled 483 individuals with one of the following conditions: 18q‐, 18p‐, Tetrasomy 18p, and Ring 18. As a part of the ongoing longitudinal study, we collect data on living arrangements, educational level attained, and employment status as well as data on executive functioning and behavioral skills on an annual basis. Within our cohort, 28 of the 483 participants have died, the majority of whom have deletions encompassing the TCF4 gene or who have unbalanced rearrangement involving other chromosomes. Data regarding the cause of and age at death are presented. We also report on the living situation, educational attainment, and behavioral phenotype of the 151 participants over the age of 18. In general, educational level is higher for people with all these conditions than implied by the early literature, including some that received post‐high school education. In addition, some individuals are able to live independently, though at this point they represent a minority of patients. Data on executive function and behavioral phenotype are also presented. Taken together, these data provide insight into the long‐term outcome for individuals with a chromosome 18 condition. This information is critical in counseling families on the range of potential outcomes for their child.